RELASI EKSEKUTIF DAN LEGISLATIF DALAM PENETAPAN APBD KABUPATEN KUANTAN SINGINGI TAHUN ANGGARAN 2024 - Mistika, Lensi; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The timely establishment of the Regional Revenue and Expenditure Budget (APBD) is a primary prerequisite for maintaining the continuity of development and public services in the region. Delays in the establishment of the APBD, such as that which occurred in Kuantan Singingi Regency for the 2024 Fiscal Year, indicate serious problems in the relationships between local government institutions. The delay in establishing the APBD has become an important issue as it can hinder the implementation of development programs and public services in the area. This study aims to explain the relationship between the executive and legislative branches in the establishment of the APBD for the 2024 fiscal year in Kuantan Singingi Regency. The method used in this research is qualitative with a descriptive approach. Data collection techniques include interviews, documentation, and literature studies. This study utilizes interaction theory according to Stone, which is divided into four types: decisional, anticipated reaction, nondecisional making, and systemic. Research findings indicate that delays in the establishment of the regional budget (APBD) are influenced by several factors, including personal and institutional relationships between the executive and legislative branches, as well as local political dynamics. Disharmonious relationships among political elites and differing interests are major obstacles in reaching agreements related to the APBD. Conflicts regarding the proposed budget amounts are the primary cause of delays, exacerbated by weak institutional communication and the inability to build political consensus. In conclusion, the delay in the establishment of the 2024 fiscal year APBD in Kuantan Singingi Regency stems from disharmonious relationships among local government agencies, which necessitates strengthening coordination mechanisms and improving political communication capacity in the budget preparation process in the future. Keywords: Executive, Legislative, Delay, Relations, APBD